THE SCRABBLE GAME AS LEARNING MEDIA IN STUDENTS' READING OF ELEMENTARY SCHOOL: SCRABBLE GAME SEBAGAI MEDIA PEMBELAJARAN DALAM MEMBACA PERMULAAN PESERTA DIDIK SEKOLAH DASAR - Liansari, Vevy; Zulikhatin Nuroh, Ermawati (Antis Publisher, 2023)
In language, reading ability is an important basis in the learning process. Moreover, the ability to read must be mastered by every student. The implementation of offline learning after the Covid 19 pandemic, many students in elementary school especially lower grades were able to sound out letters even though they did not understand the text they were reading. Students had lack of ability to read and difficult to understand for them to receive learning material. Then, it is necessary to utilize technology which has developed rapidly every day in learning process. By bringing up new innovations regarding the Scrabble game learning media in elementary school students’ reading, this research aims to motivate the reading process of elementary school students. This game can motivate students to read vocabulary with concrete objects related to their daily life, including the environment around them. This research uses the Multimedia Development Life Cycle (MDLC) method. The results of this research show that students obtained a score of 91% (Very Good), class teachers 94% (Very Good), and 96% (Very Good) from teachers in the Computer Science Technology subject. It is proven from the results of obtaining these scores that the Scrabble game can be used as a reading support material for elementary school students.